Risk factors for labour induction and augmentation: a multicentre prospective cohort study in IndiaResearch in context - Tuck Seng Cheng; Farzana Zahir; Solomi V. Carolin; Ashok Verma; Sereesha Rao; Saswati Sanyal Choudhury; Gitanjali Deka; Pranabika Mahanta; Swapna Kakoty; Robin Medhi; Shakuntala Chhabra; Anjali Rani; et al. (Elsevier, 2024)
Summary: Background: Guidelines for labour induction/augmentation involve evaluating maternal and fetal complications, and allowing informed decisions from pregnant women. This study aimed to comprehensively explore clinical and non-clinical factors influencing labour induction and augmentation in an Indian population. Methods: A prospective cohort study included 9305 pregnant women from 13 hospitals across India. Self-reported maternal socio-demographic and lifestyle factors, and maternal medical and obstetric histories from medical records were obtained at recruitment (≥28 weeks of gestation), and women were followed up within 48 h after childbirth. Maternal and fetal clinical information were classified based on guidelines into four groups of clinical factors: (i) ≥2 indications, (ii) one indication, (iii) no indication and (iv) contraindication. Associations of clinical and non-clinical factors (socio-demographic, healthcare utilisation and lifestyle related) with labour induction and augmentation were investigated using multivariable logistic regression analyses. Findings: Over two-fifths (n = 3936, 42.3%, 95% confidence interval [CI] 41.3-43.3%) of the study population experienced labour induction and more than a quarter (n = 2537, 27.3%, 95% CI 26.4-28.2%) experienced augmentation. Compared with women with ≥2 indications, those with one (adjusted odds ratio [aOR] 0.50, 95% CI 0.42-0.58) or no indication (aOR 0.24, 95% CI 0.20-0.28) or with contraindications (aOR 0.12, 95% CI 0.07-0.20) were less likely to be induced, adjusting for non-clinical characteristics. These associations were similar for labour augmentation. Notably, 34% of women who were induced or augmented did not have any clinical indication. Several maternal demographic (age at labour, parity and body mass index in early pregnancy), healthcare utilization (number of antenatal check-ups, duration of iron-folic acid supplementation and individuals managing childbirth) and socio-economic factors (religion, living below poverty line, maternal education and partner's occupation) were independently associated with labour induction and augmentation. Interpretation: Although decisions about induction and augmentation of labour in our study population in India were largely guided by clinical recommendations, we cannot ignore that more than a third of the women did not have an indication. Decisions could also be influenced by non-clinical factors which need further research. Funding: The MaatHRI platform is funded by a Medical Research Council Career Development Award (Grant Ref: MR/P022030/1) and a Transition Support Award (Grant Ref: MR/W029294/1).